Flavor, fragrance, and odor analysis - Marsili, Ray, 1946- (CRC Press, 2012)
"Sample preparation techniques for isolating and concentrating flavor and odor-active chemicals from foods prior to GC-MS analysis continue to evolve, providing lower detection limits while being more amenable to instrumental automation. Solventless extraction techniques like solid-phase microextraction (SPME) and stir bar sorptive extraction (SBSE) have wide application appeal and are now significant problem-solving tools for flavor and odor chemists. While the first edition of Flavor, Fragrance and Odor Analysis emphasized SPME, a newer technique at the time, this edition focuses on the advantages of SBSE, including sequential SBSE and other sample manipulation techniques that increase the sensitivity and application potential of this surprisingly simple but amazingly powerful technique"-- Provided by publisher.
Keywords: Food -- Sensory evaluation.; elektronické knihy; electronic books